Relationship Between Self Esteem With Psychological Well-Being In Adolescent - MURTININGTYAS, RISKA AMELLIA, Dra. Zahrotul Uyun, M. Si (2017)
To support adolescents can develop in accordance with the stage of development or mature his mental age, so teens are expected to have a psychological well-being or abbreviated PWB is high, so that the teenager could be the generation of a strong nation, reliable and useful for many people. It is therefore important to look for factors that influence the PWB, and one of these factors is self esteem. The aim of this research is to know the relationship between self esteem with the PWB, so the authors propose the hypothesis "there is a positive relationship between self esteem with the PWB".The subject in this study is student of SMA (high school) number 2 of Sukoharjo of X grade that amount of 315 students that consist of 9 class. The sampling technique in this research is the cluster random sampling, that is the subject that made of the research sample was based on groups or classes. The measuring instrument which is used to reveal of research variables there are two kinds of measuring instrument, namely: (1) self esteem scale, and (2) the PWB scale. Data analysis in this study uses the product moment correlation. Based on the analysis results, so obtained correlation between self esteem with psychological well being (r) of 0.858 with p = 0.000 where p < 0.01, this means there is a very significant positive relationship between self esteem with psychological well being. That is, the higher self esteem then the higher psychological well being on student of SMA (high school) number 2 of Sukoharjo, and conversely the lower self esteem then lower also psychological well being on student of SMA (high school) number 2 of Sukoharjo.The empirical mean of the PWB variable is 109.2 with hypothetic mean is 90. So the empirical mean > hypothetic mean that illustrates that generally the subjects had high PWB. Furthermore the empirical mean of the self-esteem variable is 90.58 with an hypothetic mean is 87.5. So the empirical mean > hypothetic mean, that's mean in generally subjects also have high self- esteem. The role of self esteem toward the PWB (SE) amount of 73.6%, so still amount of 26.4% that affects the PWB beside self-esteem, for example: social support, ideology of gender role, socioeconomic status, social networks, social support, religiosity, and personality.